Children with ADHD Symptomatology: Does POET Improve Their Daily Routine Management? - Frisch, Carmit; Tirosh, Emanuel; Rosenblum, Sara (Children, 2023)
Children with attention-deficit/hyperactivity disorder (ADHD) struggle with executive delays while managing their daily tasks. This is a secondary analysis of existing data from open-label research examining the efficacy of Parental Occupational Executive Training (POET). It further examines POET's efficacy in increasing young children's (3.83 to 7.08 years) executive control over daily routines, and in decreasing their ADHD symptoms. Additionally, the second analysis investigates which of the children's increased capabilities is better associated with the change in their daily routine management following the intervention. Parents of children with ADHD symptomatology (N = 72, 55 boys) received eight POET sessions. They completed standardised ADHD symptomatology, executive management of daily routines, and executive functions (EF) questionnaires at pretest, post-test, and 3-month follow-up. Children's ADHD symptoms and their management of daily routines significantly improved following the POET intervention. The children's score changes in EF accounted for 37% of the variance in their improved routine management. These findings suggest that interventions aiming to increase children's executive control over their daily routines should improve their broader array of EF besides decreasing core ADHD symptoms.